MINAT SISWA SMK N 3 PAYAKUMBUH UNTUK MELANJUTKAN STUDI KE JURUSAN KESEJAHTERAAN KELUARGA FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - Adella, Donna Canceri; Ernawati, Ernawati; Adriani, Adriani (Journal of Home Economics and Tourism, 2015)
This study aimed to describe the interest of the students of SMK N 3Payakumbuh to continue their studies to the Department of Family Welfare FT UNP.Type a descriptive study using quantitative methods. The type of data in the form ofprimary data. Data collection through questionnaires to students of class XIIdressmaking at SMK N 3 Payakumbuh. The study concluded that the interests ofstudents of SMK N 3 Payakumbuh to continue their studies to the Department ofFamily Welfare scores acquisition of each of the indicators are (1) attention to thescore of 69% with the higher category, (2) the strength of the motive on the score of62% with the higher category, (3) The sense of excitement in the category score of66% is high, but if it is seen still many who responded with fairly low category ofeach indicator, hence the need for the information and motivation given to thestudent.Keywords: Interests, Continuing Studies, SMK N 3 Payakumbuh